Investigation of the temperature effect on characteristics of the products, obtained by upgrading straight-run diesel fuel on zeolite; Химия и химическая технология в XXI веке - Bogdanov I. A. Ilya Aleksandrovich (Химия и химическая технология на иностранном языке, 2020)
Заглавие с экрана